Kinetic and structural studies on the interactions of Torpedo californica acetylcholinesterase with two donepezil-like rigid analogues. (1st January 2018) - Caliandro, Rosanna; Pesaresi, Alessandro; Cariati, Luca; Procopio, Antonio; Oliverio, Manuela; Lamba, Doriano
Abstract: Acetylcholinesterase inhibitors were introduced for the symptomatic treatment of Alzheimer's disease (AD). Among the currently approved inhibitors, donepezil (DNP) is one of the most preferred choices in AD therapy. The X-ray crystal structures of Torpedo californica AChE in complex with two novel rigid DNP-like analogs, compounds1 and2, have been determined. Kinetic studies indicated that compounds1 and2 show a mixed-type inhibition against Tc AChE, with Ki values of 11.12 ± 2.88 and 29.86 ± 1.12 nM, respectively. The DNP rigidification results in a likely entropy-enthalpy compensation with solvation effects contributing primarily to AChE binding affinity. Molecular docking evidenced the molecular basis for the binding of compounds1 and2 to the active site of β-secretase-1. Overall, these simplified DNP derivatives may represent new structural templates for the design of lead compounds for a more effective therapeutic strategy against AD by foreseeing a dual AChE and BACE-1 inhibitory activity.